The Linkage Between Personal Values and Managerial Competencies Development of Smes’ Owner-Managers in South Africa: A Conceptual Framework (Acta Universitatis Danubius. Œconomica, 2024)
This study delves into the nexus between personal values and the development of managerial competencies among owner-managers of SMEs in Durban, South Africa. Motivated by the indispensable role of managerial competencies in sustaining SMEs, despite their substantial contributions to emerging economies like South Africa, this research seeks to unveil the significance of personal values in shaping the managerial competencies of owner-managers in Durban. While acknowledging the importance of competencies, prior empirical studies have not sufficiently explored the nuanced relationship with personal values in this specific context. Employing a cross-sectional survey research design with a purely quantitative approach, the study used 248 owner or managers of SMEs in Durban as the sample size. Data analysis involved descriptive and inferential statistics, encompassing measures of central tendency and Spearman’s correlation. Key findings underscored the positive influence of personal values on the development of managerial competencies among owner-managers. Intriguingly, a negative significant relationship emerged between education levels and the managerial competencies of SME owner-managers, challenging conventional assumptions. Moreover, the study unveiled a positive and significant association between the work experience of owner-managers and their managerial competencies. Practical and managerial implications suggest the embedding of personal values among owner-managers’ employees through regular internal workshops. Furthermore, the study recommends the integration of entrepreneurship education in schools, colleges, and universities, emphasizing both entrepreneurial and managerial competencies. This research contributes to bridging the gap between theoretical insights and practical applications concerning personal values and managerial competencies in the SME sector. By shedding light on the intricate dynamics between these variables, the study enhances our understanding of the unique challenges faced by owner-managers in developing and sustaining successful SMEs in Durban.